2015
DOI: 10.1257/app.20130327
|View full text |Cite
|
Sign up to set email alerts
|

Incentives, Commitments, and Habit Formation in Exercise: Evidence from a Field Experiment with Workers at a Fortune-500 Company

Abstract: M any people state a desire to change health-related behaviors, yet struggle to do so. These behavioral problems in domains such as weight loss, smoking, and exercising have helped to motivate a rich literature in economics on time-inconsistent behavior (Strotz 1955(Strotz -1956Laibson 1997; Rabin 1999, 2001;Loewenstein, O'Donoghue, and Rabin 2003;DellaVigna and Malmendier 2006). This literature has shown that time inconsistency can generate patterns of behavior that lead to both "internalities," where one's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
143
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 44 publications
10
143
5
Order By: Relevance
“…Three of the studies were rated as being of weak quality , with one each of moderate and strong quality rating. All studies were at risk of selection bias, and studies with a weak quality rating were rated as such owing to not including a control group with similar baseline characteristics to the intervention group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the studies were rated as being of weak quality , with one each of moderate and strong quality rating. All studies were at risk of selection bias, and studies with a weak quality rating were rated as such owing to not including a control group with similar baseline characteristics to the intervention group.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies used cash payments or deductions for reaching or failing to achieve incentive goals , and another study rewarded participants with points that could be exchanged for discounts at participating businesses . Incentive periods ranged from 1 month to 5 years . The value of the incentives ranged from approximately 2016 $US38 to $US149 per month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this may be a house money effect (treating windfalls differently that money obtained through "normal" channels). Nonetheless, commitment has been documented in a wide range of settings: e.g., preference for costly single-unit packaging of tempting snacks (Wertenbroch 1998); self-imposed work deadlines with financial penalties (Ariely and Wertenbroch 2002;Bisin and Hyndman 2014); self-imposed financial penalties for smoking or drinking (Giné, Karlan, and Zinman 2010;Schilbach Forthcoming); self-imposed financial penalties for underperformance in the workplace (Kaur, Kremer, and Mullainathan 2010); selfimposed restrictions on internet access (Houser et al 2018); self-imposed restrictions on work scheduling (Augenblick, Niederle, and Sprenger 2015); and self-imposed financial penalties for failure to exercise (Royer, Stehr, and Sydnor 2015). Despite all of these examples of experimentally measured commitment demand, researchers have noted that very little pure commitment is demanded/provided in real markets (Laibson 2015).…”
mentioning
confidence: 99%
“…Examining the responses of employees during the first year of an incentive-based, exercise-focused program, Abraham and colleagues 3 reported that younger employees, females, and those reporting to be regular exercisers prior to the program launch were more likely to sign up. Royer et al 4 conducted a field experiment and studied 1,000 employees in a Fortune 500 firm. They found that gym attendance rates were doubled among those receiving an incentive ($10/visit up to 3 visits per week for 1 month) relative to a control group.…”
mentioning
confidence: 99%